(untitled) (Fiep Bulletin - online, 2019)
Abstract: Accidents with biological material are caused by many factors, with one of the primary ones being thehealthcare professional’s lack of attention and incorrect usage of the personal protective equipment (PPE). Laws have beencreated to protect this professional, as well as centers specialized to attend to these workers, informing them of the correct way tomanage the situation, from the moment of the contamination, collecting material to laboratorial examinations, to the properprophylaxis, which will be provided at no cost. The present study has as main objective to understand the profile of theprofessional who suffered an accident with biological material and was admitted in the University Hospital of Western Paranábetween January and December 2014. The study was elaborated by a quantitative, retrospective documentary analysis. Thedata acquisition was realized in a public hospital in western Paraná, through a pre-established method with ten distinct variablesconsidered relevant to this research. Which brought us the following characterizations: professionals aged 22 to 41 were themost frequently involved, most of them were nursing technicians, female, exposed by intravenous administration, vaccinatedagainst Hepatitis B, residing in Cascavel/PR.